MINERALOGICAL AND CHEMICAL CHARACTERISTICS OF SPODOSOLS IN TOBA HIGHLAND, NORTH SUMATRA - H. Prasetyo, B. (Indonesian Journal of Agricultural Science, 2009)
Spodosols are problem soils due to coarse texture, acid soilreaction, low nutrient status, and low soil moisture retention.About 2.16 million ha of Spodosols (1.1% of the Indonesianland areas) distributed in lowland and highland areas inKalimantan, Sumatra, Sulawesi, and Papua. Spodosols of theToba highland areas require special attention because theseforested lands are gradually cleared, but then abandoned becausethey are not suitable for agricultural development, causing landdegradation. This study aimed to evaluate mineralogical andchemical characteristics of Toba highland Spodosols, NorthSumatra, and their implication on agricultural development.Three pedons of the Toba highland Spodosols from HumbangHasundutan regency were studied, consisted of soils developedfrom volcanic sand overlying liparite tuff under the influenceof low temperature and high rainfall. Field observation wasconducted in January 2008. Fifteen soil samples were collectedfrom the three pedons based on the depth of soil horizon.Results indicated that the formation of these Spodosols wereinfluenced by parent material, high elevation (1676-1821 mabove sea level), and by high amount of rainfall (2167 mm).The Spodosols in Toba highland were still in the early stage ofdevelopment as characterized by shallow effective soil depth(22-23 cm), domination of weatherable minerals (39-81%) inthe sand fraction and dominated by amorphous mineral asshown by sum of A1 + 1/2 Fe extracted by ammonium oxalateas much as 0.6-12.8%. The Spodosols were also characterizedby coarse texture (66-95% sand fraction in E and B horizons),high organic-C content (1.4-37.7%), acid soil reaction (pH 3.7-5.3), very high K2O in Oa horizon (552-933 mg kg-1) and Bspodic or C horizon (812-2028 mg kg-1), and low base saturation(< 5%). The existence of biological processes in the surfacelayer was indicated by accumulation of exchangeable bases(0.88-1.14 cmolc kg-1 in Oa horizon and 0.09-0.25 cmolc kg-1in B horizon), P2O5 (181-298 mg kg-1 in Oa horizon and 3-24 mg kg-1in E horizon), and K2O (552-933 mg kg-1 in Oa horizon and 13-30 mg kg-1 in E horizon). However, these nutrients were easilyleached after deforestation. With the sandy texture, loosestructure, and no vegetation cover, the erosion hazard is highin the deforested areas. Therefore, lands with Spodosols of theToba highland, especially are not recommended for agriculturaldevelopment, rather they should be kept as forest lands.